Flood warning and monitoring system (FWMS) using GSM technology / Nurzaid Muhd Zain... [et al.] - Muhd Zain, Nurzaid; Elias, Lidia Shahira; Paidi, Zulfikri; Othman, Mahfudzah (UiTM Cawangan Perlis, 2020)
Floods are natural disasters that occur due to climate factors. The impact of floods on property and lives can be too high, resulting in the need to establish a monitoring system. FWMS is a personal flood monitoring system that has the ability to call and send warning via SMS. The warning was sent to not only system users, but also directly to the Fire and Rescue Station as floodwaters rose rapidly to dangerous levels. FWMS is developed using Arduino Uno microcontroller, ultrasonic sensor (HC-SR04) and GSM SIM900A module. Using FWMS, users can apply for flood status in their area in real time via SMS. In FWMS, there are three different levels of flood warning system. The first is the "normal" level, when the situation is normal. The second is the "warning" level, where an SMS will be sent to the users each time a flood is detected. Meanwhile, the third is known as the "danger" level, which will be sent when the depth of the flood that occurs is detected to be higher. For both levels of "warning" and "danger", a loud buzzer will be issued as a warning sound notification to users. Three types of tests were performed on the FWMS to measure its level of performance. These tests were functional tests, prototype system tests, and GSM network performance tests. They were done to ensure that FWMS can be used and function properly as required. The tests have produced positive results and it is potentially to be further enhanced.